Developing a Mental Illness Nursing Diagnoses subSET: study protocol for a e-delphi survey (MINDSET study) - Claudia Fantuzzi; Valentina Zeffiro; Gianfranco Sanson (Dissertation Nursing, 2024)
Introduction: Nursing care, despite constituting a significant portion of healthcare costs, often remains overlooked in healthcare data systems, which primarily focus on medical data. Incorporating standardized nursing language (SNL) into electronic health records has shown promise in predicting outcomes across various clinical settings. However, nurses' unfamiliarity with standardized terminologies poses a significant barrier to their implementation. NANDA-International (NANDA-I) nursing diagnoses (NDs) offer a standardized framework, yet their application in mental health (MH) settings remains underexplored.